2022
DOI: 10.1128/aac.01793-21
|View full text |Cite
|
Sign up to set email alerts
|

Model-Based Meta-Analysis of Relapsing Mouse Model Studies from the Critical Path to Tuberculosis Drug Regimens Initiative Database

Abstract: Tuberculosis (TB), the disease caused by Mycobacterium tuberculosis  ( Mtb ), remains a leading infectious disease-related cause of death worldwide, necessitating the development of new and improved treatment regimens. Non-clinical evaluation of candidate drug combinations via the relapsing mouse model (RMM) is an important step in regimen development, through which candidate regimens that provide the greatest decrease in probability of relapse following treatmen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…These binned annotations were consistent with the combination treatment improvement estimated in an interstudy comparison using a mixed-effects logistic regression model approach to normalize the differences in study methodologies. 16 Principal-component (PC) analysis (PCA) revealed partial separation of +C1 and −C1 combinations along the first PC, indicating a strong predictive signal in pairwise data and suggesting that linear combinations of in vitro pairwise drug responses may be sufficient to distinguish drug combinations with different in vivo outcomes, even in the absence of trained supervised learning models. Notably, the signal was robust to the number of drugs involved in a combination, as we observed separation between 3-drug and 4+-drug combinations along the second PC, which was orthogonal to the first ( Figure S2 A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These binned annotations were consistent with the combination treatment improvement estimated in an interstudy comparison using a mixed-effects logistic regression model approach to normalize the differences in study methodologies. 16 Principal-component (PC) analysis (PCA) revealed partial separation of +C1 and −C1 combinations along the first PC, indicating a strong predictive signal in pairwise data and suggesting that linear combinations of in vitro pairwise drug responses may be sufficient to distinguish drug combinations with different in vivo outcomes, even in the absence of trained supervised learning models. Notably, the signal was robust to the number of drugs involved in a combination, as we observed separation between 3-drug and 4+-drug combinations along the second PC, which was orthogonal to the first ( Figure S2 A).…”
Section: Resultsmentioning
confidence: 99%
“…BPaL is established as better than the SOC for both decreasing disease relapse and shortening treatment time of mice infected with drug-sensitive M. tuberculosis . 6 , 16 , 17 In addition, the use of BPaL has dramatically shortened the treatment time of MDR-TB in the clinic. 5 We, therefore, chose BPaL as a benchmark for further treatment improvement over the SOC in the RMM, despite not yet knowing the outcome of BPaL over the SOC in clinical trials for drug-sensitive TB (DS TB) treatment.…”
Section: Resultsmentioning
confidence: 99%
“…All the data on drug activity against drug-tolerant Mtb, ranging from the most studied in vitro Wayne dormancy model [ 40 ] to the papers on the sterilization of non caseum- [ 83 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 ] and caseum-forming [ 97 , 102 , 103 ] mice, shed a new light on TB biology [ 129 , 130 ]. These and other preclinical efficacy studies have shown that the greatest difficulties in curing TB do not depend only on intracellular AR bacilli and of their mutants but, above all, on extracellular NR drug-tolerant bacilli living in the caseous tuberculomas [ 4 ], the hallmark of TB.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, these studies confirmed that the successful treatment of active TB requires the use of drug combinations to eradicate the diverse populations of bacteria present in the infected host [ 129 ]. The proportion of non caseum- and caseum-forming mice not exhibiting relapses following different treatments appeared to be useful in selecting candidate drug combinations for clinical evaluation as TB drug regimens [ 130 ].…”
Section: Discussionmentioning
confidence: 99%
“…One strategy successfully used to identify effective partner agents capable of contributing to treatment shortening, is to evaluate bactericidal and sterilizing activity of drug combinations in both the presence and absence of the new partner agent (for examples see, (10)(11)(12)(13)). Regimens can then be rank ordered based on performance by one or both treatment outcomes as quantitative measures of the contribution of the new partner agent (14).…”
Section: Introductionmentioning
confidence: 99%